The Effectiveness of Circle Adventure Educational Game in Enhancing Student’s Problem-Solving Skills on Circle Topics among Grade XI - Mulyasa, I Made Artha; Ariawan, I Putu Wisna; Parwati, Ni Nyoman (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2025)
The development of game-based mathematics learning media serves as a strategic means of improving problem-solving skills among grade XI students in learning circle concepts. This research aims to produce RPG Maker MV-based learning media that is valid, practical and effective in improving problem solving for class XI circle material. This research uses a development method with the ADDIE model which consists of five stages, namely Analysis, Planning, Development, Implementation, and Evaluation. There are 2 (two) tests carried out, namely through formative evaluation with research success criteria, post-test and pre-test scores based on the N-Gain Test with the completeness criterion g≥30 and the Learning Goal Achievement Criteria with the completeness criterion X>40. Based on the media use effectiveness test, an N-Gain result of 0.60 was obtained with the medium category and the results of the Learning Goal Achievement Criteria with a percentage of 97.22% with the complete category based on a limited trial of 39 students of SMA Negeri 1 Singaraja.